Integrated multi-omics analyses reveal the altered transcriptomic characteristics of pulmonary macrophages in immunocompromised hosts with Pneumocystis pneumonia - Wang, Yawen; Li, Kang; Zhao, Weichao; Liu, Yalan; Li, Ting; Yang, Hu-Qin; Tong, Zhaohui; Song, Nan (Frontiers in Immunology, 2023)
With the extensive use of immunosuppressants such as glucocorticoids, immunosuppression-associated pneumonitis has received increasing attention. In these immunocompromised patients, aberrant adaptive immune responses have been considered as a key reason for opportunistic infections including Pneumocystis jirovecii pneumonia. Nevertheless, the characteristics and functions of innate immunity in these immunocompromised hosts remain unclear. Here we integrated multiplex cytokine analysis, metabolomic studies, and single-cell RNA sequencing to decipher the alterations of the innate immunity upon Pneumocystis infection with or without glucocorticoids treatment. We found that the secretion of both pro-inflammatory cytokines and metabolites in the bronchoalveolar lavage fluids (BALFs) of Pneumocystis-infected mice are impaired by glucocorticoids. We identified seven subpopulations of macrophages in mice lung tissues, and defined a group of Mmp12+ macrophages enriched in the immunocompetent mice with Pneumocystis infection, but not in the mice treated with dexamethasone. Pseudotime trajectory showed that these Mmp12+ macrophages are differentiated from Ly6c+ classical monocytes. Further, pro-inflammatory cytokines elevated in BALFs of Pneumocystis-infected mice are highly expressed in these Mmp12+ macrophages. In vitro, we confirmed that dexamethasone indeed impairs the expression of Lif, Il1b, Il6 and Tnf, as well as the fungal killing capacity of alveolar macrophage (AM)-like cells. Moreover, in patients with Pneumocystis jirovecii pneumonia, we also found a group of recruited macrophages highly resembled the aforementioned Mmp12+ macrophages based on the transcriptomic analysis, and these macrophages are inhibited in the patient receiving glucocorticoid treatment. On the other hand, dexamethasone treatment simultaneously impaired the functional integrity of resident AMs via downregulating granulocyte/macrophage colony-stimulating factor (GM-CSF) and lysophosphatidylcholine, leading to the suppressed antifungal capacities. Taken together, our study provides multiple resources for understanding the heterogeneity and metabolic changes of innate immunity in immunocompromised hosts, and also suggests that the loss of Mmp12+ macrophages population contributes to the pathogenesis of immunosuppression-associated pneumonitis.